2008
DOI: 10.1523/jneurosci.5471-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Targets the Respiration of Synaptic Mitochondria via Protein Kinase Cε

Abstract: In the brain, ischemic preconditioning (IPC) diminishes mitochondrial dysfunction after ischemia and confers neuroprotection. Activation of protein kinase C (PKC) has been proposed to be a key neuroprotective pathway during IPC. We tested the hypothesis that IPC increases the levels of PKC in synaptosomes from rat hippocampus, resulting in improved synaptic mitochondrial respiration. Preconditioning significantly increased the level of hippocampal synaptosomal PKC to 152% of sham-operated animals at 2 d of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 69 publications
(103 reference statements)
3
99
1
Order By: Relevance
“…These increases in the rate of respiration were correlated with increased levels of serine and tyrosine phosphorylation of 18 kDa subunit of complex I, threonine phosphorylation of COX IV, increased mitochondrial membrane potential, and decreased H 2 O 2 production. In addition, induction of in-vitro ischemia decreased mitochondrial cytochrome c release (Dave et al, 2008). These results suggest that after IPC, ePKC is readily available for activation in synaptosomal mitochondria on ischemia/reperfusion, in such a manner to increase mitochondrial respiration, reduce ROS production and cytochrome c release, hallmarks of reperfusion injury.…”
Section: Ischemic Preconditioning and Mitochondriamentioning
confidence: 69%
See 2 more Smart Citations
“…These increases in the rate of respiration were correlated with increased levels of serine and tyrosine phosphorylation of 18 kDa subunit of complex I, threonine phosphorylation of COX IV, increased mitochondrial membrane potential, and decreased H 2 O 2 production. In addition, induction of in-vitro ischemia decreased mitochondrial cytochrome c release (Dave et al, 2008). These results suggest that after IPC, ePKC is readily available for activation in synaptosomal mitochondria on ischemia/reperfusion, in such a manner to increase mitochondrial respiration, reduce ROS production and cytochrome c release, hallmarks of reperfusion injury.…”
Section: Ischemic Preconditioning and Mitochondriamentioning
confidence: 69%
“…In another study, ePKC levels were found to increase in the hippocampal synaptosomal fraction 48 hours after IPC (Dave et al, 2008). Treatment with a specific ePKC activating peptide 48 hours after IPC, increased the rate of oxygen consumption in the presence of substrates for complexes I, II, and IV (Dave et al, 2008). These increases in the rate of respiration were correlated with increased levels of serine and tyrosine phosphorylation of 18 kDa subunit of complex I, threonine phosphorylation of COX IV, increased mitochondrial membrane potential, and decreased H 2 O 2 production.…”
Section: Ischemic Preconditioning and Mitochondriamentioning
confidence: 91%
See 1 more Smart Citation
“…Ischemic preconditioning promoted significant increases in the levels of synaptosomal PKCε in rat hippocampus. Activation of PKCε increased synaptosomal mitochondrial respiration and phosphorylation of mitochondrial respiratory chain proteins [40] . Delivery of a PKCε inhibitory peptide abated NMDA-induced preconditioning in cell culture and isolated hippocampal slice models [41] .…”
Section: Intracellular Survival Signals and Neuroprotectionmentioning
confidence: 96%
“…5,6 Ischemic preconditioning (IPC), a paradigm where a brief ischemic insult protects the brain against a subsequent lethal ischemic injury, or treatment with the polyphenol resveratrol, has been shown to protect mitochondria and enhance levels of NAD in the brain. [7][8][9][10] The mechanism by which resveratrol and IPC regulate NAD levels has not been clearly defined. However, two key signaling pathways that may be involved are protein kinase C epsilon (PKCe) and AMP-activated protein kinase (AMPK), enzymes that regulate mitochondrial ischemic neuroprotection after IPC and resveratrol treatment.…”
Section: Introductionmentioning
confidence: 99%